KAJIAN YURIDIS MEKANISME PENANGANAN PELANGGARAN NETRALITAS APARATUR SIPIL NEGARA DALAM PENYELENGGARAAN PEMILIHAN UMUM DI KOTA BIMA TAHUN 2019 - Muhaemin, Muhaemin; Hasanah , Siti; Arzhi Jiwantara, Firzhal (IBLAM LAW REVIEW, 2023)
This research aims to find out and analyze the mechanism for resolving alleged violations of the neutrality of the State Civil Apparatus in holding general elections and to find out and analyze the follow-up to handling violations of the neutrality of the State Civil Apparatus in holding the general elections in Bima City in 2019; The method used in this research is normative-empirical legal research with a statutory approach, conceptual approach, case approach and sociological approach. Based on the results of research on the mechanism for handling violations of the Neutrality of the State Civil Apparatus in holding the general election in Bima City in 2019 involving three state institutions, namely the Regency/City Bawaslu as the entry point for reports or findings of alleged violations of the Neutrality of the State Civil Apparatus, the results of handling violations by the Regency/City Bawaslu then forwarded to the State Civil Service Commission for recommendations. The Regency/City Bawaslu recommendations are followed up by the State Civil Service Commission in the form of sanctions and recommended to the Regional Civil Service Development Officer for implementation. Regarding the imposition of sanctions and recommendations from the State Civil Apparatus Commission, Bima City Regional Civil Service Supervisory Officers were not implemented in accordance with the recommendations, they were implemented according to the recommendations of the State Civil Apparatus Commission.